Ascent trajectories from the lunar far-side to Earth–Moon L2 halo orbits. Issue 11 (1st December 2015) - Dietrich, Ann; Davis, Kathryn; Parker, Jeffrey
Abstract: This paper examines various design parameters for missions that ascend from the lunar far-side surface and insert into a halo orbit about the Earth–Moon L2 point. These parameters include fuel costs, ascent sites of interest such as the South Pole Aiken Basin and Tsiolkovsky Crater, different sized halo orbits, and transfer durations. Halo orbit stable manifolds are studied in the simplified Circular Restricted Three-Body Problem, and transfers are targeted and optimized in high-fidelity simulations. The design parameters studied in this paper can aid in development of mission architectures in the Earth–Moon system as well as other systems with a secondary mass without an atmosphere.